2009
DOI: 10.1080/00207450903192852
|View full text |Cite
|
Sign up to set email alerts
|

IQ Predicts Neuropsychological Performance in Children

Abstract: In children, IQ predicts neuropsychological performance differentially based upon ability level, with stronger relationships shown in lower IQ ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…The relatively low but significant correlations between IQ and naming accuracy scores are consistent with correlations between IQ and neuropsychological test performances previously reported for both adults (Diaz-Asper, Schretlen, & Pearlson, 2004) and children (Foley, Garcia, Shaw, & Golden, 2009), reflecting an expected, relative consistency between general intellectual function and performance in particular cognitive domains. Correlations between WIAT word reading and several ANT, yet no VNT scores, reached significance.…”
Section: Discussionsupporting
confidence: 88%
“…The relatively low but significant correlations between IQ and naming accuracy scores are consistent with correlations between IQ and neuropsychological test performances previously reported for both adults (Diaz-Asper, Schretlen, & Pearlson, 2004) and children (Foley, Garcia, Shaw, & Golden, 2009), reflecting an expected, relative consistency between general intellectual function and performance in particular cognitive domains. Correlations between WIAT word reading and several ANT, yet no VNT scores, reached significance.…”
Section: Discussionsupporting
confidence: 88%
“…It has been demonstrated that a high cognitive reserve is a protective factor in schizophrenia, bipolar disorder, depression, and traumatic brain injury 38,39. From the perspective of task execution, intelligence can positively affect retrieval and the application of previous learning, and can play a protective role to compensate for impaired attention and memory 37,41. This may explain our finding that narcoleptics with a high IQ experience less cognitive impairment and are less depressed.…”
Section: Discussionmentioning
confidence: 74%
“…While no interactions between performance and family history status related to brain activity in either the DLPFC or the cerebellum, there was a significant relationship between RT on risky versus safe selections and BOLD response in the DLPFC, regardless of family history status [overall model R 2 = 0.49, F (3, 27) = 8.55; RT: β = .37, t (27) = 2.62, p < 0.05]. Furthermore, given the relationship between intelligence and executive functioning (Foley et al., 2009), we examined whether IQ correlated with DLPFC activity during risky decision‐making. No significant relationship between IQ and DLPFC activity was present [overall model R 2 = 0.02, F (1, 29) = 0.56, β = −.14, t (29) = −.75, p > 0.05].…”
Section: Resultsmentioning
confidence: 99%